1975
DOI: 10.1002/pol.1975.170131223
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur‐containing polymers. XVI. Oxidative coupling of dithiols with various diacyl disulfides

Abstract: Previously we have reported' that bis(oxycarbony1) disulfides (I) react with dithiols in the presence of triethylamine to give disulfide polymers in accord with eq. (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…It has been reported that thiols would react with tetra- alkylthiuram disulfides to yield dialkylammonium dialkyldithiocarbamate and the disulfide derivative (derived from the thiol) quantitatively under mild conditions. 39 As expected, after MCE and TDS were mixed for 5 min, the disulfide derivative, 2-hydroxyethyl disulfide (HEDS), and diethylammonium diethyldithiocarbamate (DDDC), rather than TDS and MCE themselves, were observed in the 1 H NMR and highperformance liquid chromatography−mass spectrometry (HPLC-MS) measurements (SI Figure S3), indicating a rapid, complete oxidation reaction. Since the reaction was too fast for NMR and HPLC to monitor, we employed UV− vis absorption spectroscopy to investigate the reaction kinetics (SI Figure S4) and calculated the rate constant of thiol oxidation (k 1 ) using the well-known kinetic eq (SI eq S3c).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…It has been reported that thiols would react with tetra- alkylthiuram disulfides to yield dialkylammonium dialkyldithiocarbamate and the disulfide derivative (derived from the thiol) quantitatively under mild conditions. 39 As expected, after MCE and TDS were mixed for 5 min, the disulfide derivative, 2-hydroxyethyl disulfide (HEDS), and diethylammonium diethyldithiocarbamate (DDDC), rather than TDS and MCE themselves, were observed in the 1 H NMR and highperformance liquid chromatography−mass spectrometry (HPLC-MS) measurements (SI Figure S3), indicating a rapid, complete oxidation reaction. Since the reaction was too fast for NMR and HPLC to monitor, we employed UV− vis absorption spectroscopy to investigate the reaction kinetics (SI Figure S4) and calculated the rate constant of thiol oxidation (k 1 ) using the well-known kinetic eq (SI eq S3c).…”
Section: Resultssupporting
confidence: 54%
“…The 2-mercaptoethanol (MCE) and TDS were selected to study the oxidation reaction. It has been reported that thiols would react with tetra-alkylthiuram disulfides to yield dialkylammonium dialkyldithiocarbamate and the disulfide derivative (derived from the thiol) quantitatively under mild conditions . As expected, after MCE and TDS were mixed for 5 min, the disulfide derivative, 2-hydroxyethyl disulfide (HEDS), and diethylammonium diethyldithiocarbamate (DDDC), rather than TDS and MCE themselves, were observed in the 1 H NMR and high-performance liquid chromatography–mass spectrometry (HPLC-MS) measurements (SI Figure S3), indicating a rapid, complete oxidation reaction.…”
Section: Resultsmentioning
confidence: 79%
“…Bis(oxycarbonyl)disulfide reacts with dithiols in the presence of triethylamine to give disulfide polymers [173]: Other than bis(oxycarbonyl) disulfides, compounds such as thiuram disulfides, dixanthogens and bis(carbomyl) disulfides were also used to prepare disulfide polymers [174]. Alternating as well as random copolymers have also been prepared using this method [175,176].…”
Section: Oxidative Coupling Of Dithiols With Diaeyl Disulfidesmentioning
confidence: 99%